Histories lived on the teaching staff in the digital world (Praxis Educativa, 2012)
This paper has the purpose of contributing evidence about the complexity to which the schools and the teaching staff have to afford when they have to deal with the changes of Technologies of Information and Communication (TIC) and their educational use. We begin with the presentation of the investigation from which this text comes and argue that the professional histories of life constitute important evidence to understand what is happening at schools. Then, we focus on the situation of the TIC in education. All the teachers who participate in this investigation, except one, said that TIC were the cause of transformations and important changes for education and also an object of personal and professional questions and reflection, whether they were used in the classroom or not. That is why we studied this topic from three different angles. In the first place, we briefly referred to how the TIC are changing the way in which people relate with information and how they place themselves in front of learning; to face difficulties of education systems and start using TIC oriented to get an improvement of school and the learning process of students and teachers. Finally, and before the conclusions, we take some extracts of the professional lives of eleven teachers that offer their experience corporized in relation with the TIC.
Keywords: professional histories; narrative; TIC; transformations